PENGARUH TASK-TECHNOLOGY FIT TERHADAP KINERJA INDIVIDUAL PADA MAYA SANUR RESORT & SPA - Putra, I Gusti Ngurah Agung Dananjaya; Juliarsa, Gede (E-Jurnal Akuntansi, 2016)
The aim of this study was to determine the effect of task-technology fit against individual performance at Maya Sanur Resort & Spa. This research was done in Maya Sanur Resort & Spa by using a sample of 41 respondents. Methods of data collection using the questionnaire. The data analysis technique used in this study is a simple linear regression analysis. Results from this study indicate that the task-technology fit affect the individual's performance, proven by significance value less than 5%. Thus it can be seen that the influence of task-technology fit to the individual performance are categorized either.
Keywords: Task-Technology Fit, Employee Performance, Information System Technology